Pengembangan Sistem Informasi Rekam Medis Studi Kasus: Klinik Mutiara Sehat Malang - Masrur Anwar; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Klinik Mutiara Sehat is a first phase health facility clinic that cooperate with BPJS Kesehatan. In performing health services, support of information technology in the management of information is required to improve the services. This research development of medical record information system begins by performing a requirement analysis to get the capability of medical record information system which is then modeled into use case diagram. And then, from the results of recruitment analysis done several types of medical records information system design is modeling with UML notation, database design and web service design. Then, the implementation of the system design that produces Medical Record Information System based website that provides integrated medical record service function with BPJS Health and medical record management of examination results. Furthermore, from the results of the implementation of Medical Record Information System carried out system testing which states that the system developed to run in accordance with needs analysis that has been defined in the recruitment analysis.